Очистка и свойства двух форм лейцил-тРНК-синтетазы из миокарда свиньи - Стапуленис, Р.Р.; Иванов, Л.Л.; Лукошявичюс, Л.Ю.; Ярмоленко, В.В.; Прашкявичюс, А.К. (Биополимеры и клетка, 1986)
Описан метод выделения из миокарда свиньи свободной и ассоциированной с другими аминоацил-тРНК-синтетазами форм лейцил-тРНК-синтетазы и проведено сравнение ряда их физико-химических свойств. Установлено, что лейцил-тРНК-синтетазная активность в составе высокомолекулярного комплекса более устойчива к термоинактивации. Описано метод виділення з міокарда свині вільної і асоційованої з іншими аміноацил-тРНК-синтетазами форм лейцил-тРНК-синтетази та проведено порівняння низки їхніх фізико-хімічних властивостей. Встановлено, що лейцил-тРНК-синтетазна активність у складі високомолекулярного комплексу більш стійка до термоінактивації. A method for isolation and purification of two forms (E1 and E2) of leucyl-tRNA synthetase (LeuRS) from pig myocardium is described. E1 is a free enzyme with molecular weight of 158000. E2 is a complex of aminoacyl-tRNA synthetases with molecular weight of 840000. The values of sedimentation constants were 8S for E1 and 32S for E2. The effect of K⁺ and kinetic parameters of the aminoacylation reaction for the both forms of the enzyme are studied. The Km values of EI for ATP and leucine were greater and for tRNA were lower than those of E2. The evaluation of thermal conformatiotial transitions of two forms of LeuRS is carried out. According to the intrinsic protein fluorescence method, the midpoint of denaturation transition for E1 and E2 is in the temperature range between 4 and 44 °C. LeuRS activity of the high-molecular weight complex is more resistant to thermal inactivation than that of free enzyme.